Z PENGARUH RISIKO BISNIS, FINANCIAL DISTRESS, DAN KEBIJAKAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN PERAN RESEARCH AND DEVELOPMENT SEBAGAI VARIABEL MODERASI: Studi Empiris pada Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Zuriyah Toyibah; Endang Ruhiyat (Politeknik Negeri Jakarta, 2023)
This study aims to determine the effect of business risk, financial distress, and investment policies on firm value with the role of research and development as a moderating variable in financial companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling method in this study used the purposive sampling method, so that a research sample of 15 financial companies listed on the Indonesia Stock Exchange in 2017-2021 was obtained. Data analysis was performed by panel data regression method and moderated regression analysis using eviews 10. The results of this study indicate that business risk, financial distress, and investment policies are statistically proven to have a partial effect on firm value. Research and development can moderate the effect of investment policy on firm value, while research and development cannot moderate the effect of business risk and financial distress on firm value.